(untitled) (Bangladesh Pharmaceutical Journal, 2024)
Blood borne infections are one of the major health problems in Bangladesh, which requires frequent use of antimicrobials. In most of the cases, diagnosis and treatment with such antimicrobials are done empirically. Therefore, updated information on etiological data for major pathogens and their pattern of antibiotic resistance is required for formulating strategy and guideline for the prescribers. This study was carried out to assess the pattern of antibiotic resistance and to determine the prevalence of resistance phenotypes of different bacterial pathogens, including Acinetobacter sp. previously collected from patients from a hospital in Dhaka, Bangladesh. Retrospective analysis of 573 clinical records was performed, and the antimicrobial susceptibility pattern of those records was used to determine the prevalence of the isolates that were multi-drug resistant. Our finding indicates that Acinetobacter sp. (12%), followed by Salmonella typhi (58%) were the second most often found pathogen in the blood samples. In addition, we identified that these organisms exhibited a multi-drug resistance (MDR) pattern toward the most frequently used antibiotic classes, including cephalosporin, fluoroquinolones, aminoglycosides and carbapenems. We found moderate to high levels of resistance against aminoglycosides (45-53%), cephalosporins (28-45%), fluoroquinolones (28-39%) and carbapenem (17- 19%) in Acinetobacter sp. (11.7%, n = 67), as well as multi-drug resistant (66.7%, n = 38), and extensively drug-resistant or XDR (13.64%, n = 9), isolates. We also found pan-drug resistant (PDR) isolates (2.3%) of Acinetobacter sp. showing resistance against all antibiotics that are used clinically. In order to launch effective treatment strategies and prevent the further emergence of MDR, it can be suggested that extensive national antimicrobial surveillance be conducted against these pathogens. There is also a need for further characterization of such superbugs to address the issue of antimicrobial resistance. Bangladesh Pharmaceutical Journal 27(1): 67-72, 2024 (January)